Local order of Pb1-xLaxZr0.40Ti 0.60O3 ferroelectric ceramic materials probed by X-ray absorption and Raman spectroscopies - Mesquita, A. [UNESP]; Michalowicz, A.; Pizani, P. S.; Provost, K.; Mastelaro, V. R. (Elsevier, 2014)
This paper reports on the structural characterization of Pb 1-xLaxZr0.40Ti0.60O3 (PLZT) ferroelectric ceramic compositions prepared by the conventional solid state reaction method. X-ray absorption spectroscopy (XAS) and Raman spectroscopy were used to probe the local structure of PLZT samples that exhibits a normal and relaxor ferroelectric behavior. From the Zr K-edge and Pb LIII-edge EXAFS spectra, a considerable dissymmetry of Zr and Pb sites was observed in all samples, including those showing a long-range order cubic symmetry and a relaxor behavior. The Raman spectroscopy results confirmed the existence of a local disorder in all PLZT samples through the observation of Raman active vibrational modes. The variation in the intensity of the E(TO 3) mode in the PLZT relaxor samples indicates that the process of correlation between nanodomains stabilizes at temperatures lower than T m. © 2013 Elsevier B.V. All rights reserved.
Keywords: EXAFS; Ferroelectrics; PLZT; Raman; Relaxor; Long range orders; Plzt; Relaxor ferroelectric; Relaxors; Solid state reaction method; Structural characterization; Ferroelectric materials; Raman spectroscopy; Solid state reactions; X ray absorption spectroscopy; Zirconium; Lead